2015
DOI: 10.1007/s11270-015-2601-5
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Development of Radiocaesium and Radiostrontium Concentrations in the Hydrosphere—Methods of Evaluation

Abstract: A significant amount of artificial radionuclides has been introduced into the environment in the last century during atmospheric nuclear weapons tests and the Chernobyl accident. In this study, we investigated the temporal changes of concentrations and amounts of these radionuclides ( 90 Sr and 137 Cs) in surface water and river bed sediments. In order to evaluate the artificial radionuclide contamination diminution, we used and compared two different approaches: using a kinetic equation of the first order and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 13 publications
(17 reference statements)
0
8
0
1
Order By: Relevance
“…Bylo pozorováno, že od doby vniknutí těchto radionuklidů do životního prostředí jejich množství průběžně klesá, a to v důsledku jejich radioaktivní přeměny i různých migračních jevů. V České republice jsou v současnosti hodnoty velmi nízké, ale měřitelné [5,13,[17][18][19][20][21].…”
Section: Vtei/ 2021/unclassified
See 1 more Smart Citation
“…Bylo pozorováno, že od doby vniknutí těchto radionuklidů do životního prostředí jejich množství průběžně klesá, a to v důsledku jejich radioaktivní přeměny i různých migračních jevů. V České republice jsou v současnosti hodnoty velmi nízké, ale měřitelné [5,13,[17][18][19][20][21].…”
Section: Vtei/ 2021/unclassified
“…It has been observed that since the introduction of these radionuclides into the environment their amount has been gradually on the decline as a result of radioactive transformation of the monitored radionuclides and various migration phenomena. Radionuclide values in the Czech Republic are currently very low but still measurable [5,13,[17][18][19][20][21].…”
Section: Metodikamentioning
confidence: 99%
“…The radiological situation in the Baltic Sea changed after the Chernobyl Nuclear Power Plant (ChNPP) accident, which became the main source of 137 Cs after 1986 (Ikäheimonen et al, 2009;Juranová et al, 2015). After the accident, an average activity concentration of 137 Cs in the surface waters of the Baltic Sea grew by more than an order of magnitude relative to the radioactive background (12 Bq·m -3 ) formed after nuclear weapons tests in the atmosphere (Styro et al, 1990).…”
Section: Review Of Literaturementioning
confidence: 99%
“…In more recent proles, 18 though dependent on sampling location, radiocesium concentration appears to peak below the surface layer with a more gradual falloff beyond the peaks suggesting a downward migration over time. Very few studies document the temporal changes of radiocesium in surface sediments 19,20 and so far in Fukushima, no known studies have attempted to evaluate such changes in agricultural ponds. However, evaluating the decreasing rate of radiocesium in bottom sediments is important because sediments account for the largest proportion of the total radiocesium concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Temporal changes in radiocesium concentration can be quantied by the effective half-life which accounts for both physical decay and ecological processes 20,22,23 or the ecological half-life which excludes physical decay. 24 effective or ecological half-lives of radiocesium 6,19,20,[22][23][24] in either soil or sediments were evaluated from sediment samples thereby providing values for discrete points. Sediment sampling underwater is labour-intensive, long, and becomes expensive for wide area coverage.…”
Section: Introductionmentioning
confidence: 99%